Global Pandemics Corona Virus (COVID-19) Pandemonium Disruption Educational Sector Blues and Global Issues Arising Therefrom (Global Journal of Science Frontier Research, 2020)
In this paper, we survey the topic of pandemics with specific reference to the Global Corona Virus pandemic which is dubbed COVID-19, and we trace the background of pandemics in the past. Our objective in this paper is to share our experiences as well as to examine the impact of the pandemic on businesses, especially the educational sector, and also on other sectors. In this paper, we take a multidisciplinary approach as well as a compendious approach of surveying a broad swathe of issues. At the same time, we use a narrative approach, providing commentaries and descriptive analysis, and a flashback of history in the literature review. We rely mainly on secondary data for the discussion and analysis as the nature of the topic is still fresh and delicate for us to conduct primary research. Besides, we believe that the problem at hand is on-going, all encompassing, and it may be premature at this stage for us to come to some definitive conclusions. The theoretical model which we use in the analysis is the macro-environmental model which is popularly and variously called the PEST, PESTLE, PESTEL, SLEPT, or STEEPLE model, popular in management studies and used by Social Scientists in their exegesis and discourses.
Keywords: climate change; recession; depression; quantitative easing